2009
DOI: 10.1111/j.1467-9299.2008.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

Narratives and Dilemmas of Local Bureaucratic Elites: Whitehall at the Coal Face?

Abstract: The worlds of local bureaucrats are under researched and under theorized compared with those of civil servants in core executives. Yet local bureaucratic elites, sitting as they do between central states and localities, are key actors in governance networks. In England, the role and responsibilities of local bureaucratic elites has been transformed since the days of professionalized officers heading departmental structures reporting to committees, firstly by NPM and politicization in the 1980s and 1990s and, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
(36 reference statements)
0
10
0
Order By: Relevance
“… Survey responses are open to the accusation that respondents reveal ‘stated preferences’ and not their ‘true preferences’; however the survey responses discussed here triangulate with the qualitative interview and case study evidence gathered alongside these survey data and reported in Stoker et al. (2003); Gains (2006); Gains (forthcoming). …”
mentioning
confidence: 64%
“… Survey responses are open to the accusation that respondents reveal ‘stated preferences’ and not their ‘true preferences’; however the survey responses discussed here triangulate with the qualitative interview and case study evidence gathered alongside these survey data and reported in Stoker et al. (2003); Gains (2006); Gains (forthcoming). …”
mentioning
confidence: 64%
“…Researchers wishing to research elites and other actors in governance settings can choose whether to treat ethnography as a 'method', or as an interpretivist 'methodology' in line with their ontological disposition in order to chart their research approach. So, for example, writing in this journal on the traditions and dilemmas of local bureaucratic elites following constitutional change in 10 local authorities, this author drew on ethnographic methods (interviews with all key stakeholders, observations of public and private meetings, policy tracking and documentary analysis (Gains 2009). Adopting a 'constructivist modern empiricism' the argument challenged (deterministic) academic assumptions about the impact these new rules would have on bureaucratic behaviour.…”
Section: Ethnography: Methods or Methodology?mentioning
confidence: 99%
“…On the one hand one could argue that the results so far have been disappointing. Bevir and Rhodes deliberately aim their work at (British) political science, but after ten years, three books, and numerous articles and replies to critics, there are only a few political scientists who have applied the conceptual apparatus of British interpretivism to the problematics of governance (Sullivan 2007, Gaines 2009). Also, as far as I know, no books have so far been published that contain exemplars of British interpretivism in practice.…”
Section: Substantive Conceptsmentioning
confidence: 99%